Fast High-Resolution Simulation of the Gross Slip Wear of Axially Symmetric Contacts - Dimaki A. V. Andrey Viktorovich; Dmitriev A. I. Andrey Ivanovich; Menga N.; Papangelo A.; Ciavarella M.; Popov V. L. Valentin Leonidovich (2016, 2016)
Title screen